Caderno de Projetos- A book of PROJECT propositions suggestions dedicated to Venice City and her surroundings (P. Nazareth Ed., 2013)
Caderno de Projetos- A book of PROJECT propositions suggestions dedicated to Venice City and her surroundings.
English; Italian
Keywords: N7560-8266 Visual Arts. Special subjects of art; Italy -- Venice